Bromate reduction by Shewanella oneidensis MR-1 is mediated by dimethylsulfoxide reductase - Wang, Yicheng; Fan, Jiale; Shen, Yonglin; Ye, Fan; Feng, Zhiying; Yang, Qianning; Wang, Dan; Cai, Xunchao; Mao, Yanping (Frontiers in Microbiology, 2022)
Microbial bromate reduction plays an important role in remediating bromate-contaminated waters as well as biogeochemical cycling of bromine. However, little is known about the molecular mechanism of microbial bromate reduction so far. Since the model strain Shewanella oneidensis MR-1 is capable of reducing a variety of oxyanions such as iodate, which has a high similarity to bromate, we hypothesize that S. oneidensis MR-1 can reduce bromate. Here, we conducted an experiment to investigate whether S. oneidensis MR-1 can reduce bromate, and report bromate reduction mediated by a dimethylsulfoxide reductase encoded with dmsA. S. oneidensis MR-1 is not a bromate-respiring bacterium but can reduce bromate to bromide under microaerobic conditions. When exposed to 0.15, 0.2, 0.25, 0.5, and 1 mM bromate, S. oneidensis MR-1 reduced bromate by around 100, 75, 64, 48, and 23%, respectively, within 12 h. In vivo evidence from gene deletion mutants and complemented strains of S. oneidensis MR-1 indicates that MtrB, MtrC, CymA, GspD, and DmsA are involved in bromate reduction, but not NapA, FccA, or SYE4. Based on our results as well as previous findings, a proposed molecular mechanism for bromate reduction is presented in this study. Moreover, a genomic survey indicates that 9 of the other 56 reported Shewanella species encode proteins highly homologous to CymA, GspD, and DmsA of S. oneidensis MR-1 by sequence alignment. The results of this study contribute to understanding a pathway for microbial bromate reduction.